AN ALTERNATIVE USAGE OF URTICA DIOICA AS ADSORBENT FOR MALACHITE GREEN: OPTIMIZATION STUDY - ERTAN, Bengü; GURKOK, Sumeyra; EFE, Derya (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The adsorption of malachite green (MG) by the use of an eco-friendly adsorbent Urtica dioica (U. dioica) has been reported in the present study. The effects of different parameters were tested on MG adsorption and optimization of the effective parameters (pH, temperature and initial dye concentration) were performed by response surface methodology (RSM). Maximal adsorption yield of 91.67% was achieved at pH 6.5 and 50 °C with 200 mgL-1 initial dye concentration. The isotherm and kinetic studies were employed to describe the adsorption process. The experimental data fitted better on the Freundlich model and the adsorption process followed by the pseudo-second order model.